Treatment of neuropathic pain: a new method, transdermic route - Vittorio Iorno; Vincenzo Moschini (Publiediting, 2006)
The therapy of neuropathic pain is difficult due to the lack of reliable classification. This pain can be defined as peripheral, central, mixed or based on the underlying mechanisms. Following this last criterium, we selected 44 patients affected by peripheral neuropathic pain. The not invasive care consisted in giving a pharmacological cocktail by a transdermal hydroelectrophoretic technique. 34% of all patients showed a pain relief between 70 and 99% (good results), while 9% had a complete resolution of pain (very good results). We concluded suggesting the transdermic hydroelectrophoretic techniques as useful and efficient in drugs administration to patients with peripheral neuropathic pain.